Case Report: Magnetic Resonance Imaging Features of Scrotal Angiomyofibroblastoma (AMF) With Pathologic Correlation - Zeng, Jing; Zhang, Lingtao; Shi, Changzheng; Luo, Liangping (Frontiers in Surgery, 2022)
Angiomyofibroblastoma (AMF) is a rare benign myofibroblastic tumor that mainly occurs in the genital tract of middle-aged female patients. However, it can also arise in scrotum, spermatic cord and bladder. We described herein a case of 42-year-old patient who was admitted to our hospital with a left scrotal mass. Imaging examinations showed that the mass had abundant vessels and displayed obvious progressive intensification on enhanced MRI. The following histopathological and immunohistochemical studies led to the diagnosis of AMF. Here we describe the magnetic resonance imaging findings of a case of scrotal AMF. We hope that the information can help radiologists to identify AMF.